THE ROLE OF SODIUM-GLUCOSE COTRANSPORTER-2 (SGLT2) INHIBITORS IN ACUTE MYOCARDIAL INFARCTION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This article analyzes the impact of sodium-glucose cotransporter-2 (SGLT2) inhibitors, particularly empagliflozin, on the course of acute myocardial infarction (AMI) in patients with type 2 diabetes mellitus (T2DM). Data are presented on the high prevalence of T2DM and its association with cardiovascular complications. The cardioprotective mechanisms of SGLT2 inhibitors are discussed, including the reduction of preload and afterload, improvement of myocardial metabolism, and antioxidant and anti-inflammatory effects. Randomized clinical trials (EMPA-REG OUTCOME, EMPEROR-Reduced) have demonstrated a reduction in cardiovascular mortality and hospitalization rates with SGLT2 inhibitors. However, their use in the acute phase of AMI remains insufficiently studied. The authors emphasize the need for further research to determine the optimal timing and conditions for their administration.
Keywords: type 2 diabetes mellitus, acute myocardial infarction, complications, cardioprotection, treatment, sodium-glucose cotransporter-2 inhibitors, empagliflozin.